The "greater goods" response to the argument from divine hiddenness - Teeninga, L (2018)
Arguments from divine hiddenness attempt to demonstrate that the apparent hiddenness of God is a reason for thinking God does not exist. One of the most prominent arguments from divine hiddenness maintains that if God existed He would do what He could to ensure that all persons have access to conscious personal relationship with Him. But since such relationship is impossible for those who do not believe God exists, God would ensure that everyone has evidence sufficient to believe that He exists. That there are people who do not believe God exists due only to a lack of evidence is therefore a reason for thinking that God does not exist. One of the most prominent ways to respond to this kind of argument from divine hiddenness is to maintain that God withholds evidence of Himself in order to bring about some greater good or another. But there are a few challenges facing these “greater goods” responses. First, some proposed greater goods benefit only someone other than the nonbeliever; one might argue that God would not withhold evidence sufficient for belief from one person entirely for the benefit of another person. Second, some proposed greater goods presuppose libertarian free will; but it has been argued that God would not allow such free will due to the great evil it brings about. Third, if a conscious personal relationship with God is greater than all other goods we might wonder how there could be goods for the sake of which God would be willing to withhold such relationship from some people. Finally, if God is infinitely resourceful and if all goods come from God, it is somewhat puzzling how there could be goods which preclude conscious personal relationship with God. In this thesis I aim to address these challenges to greater goods responses to the hiddenness argument.